Penerapan Strategi Kompensasi dan Motivasi pada Kinerja Karyawan di PT Alfaria Trijaya Tbk, Sampangan Kec. Gajah Mungkur Semarang - Melinda Dwi Wardani; Yuniarto Rahmad Satato (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the impact of compensation and motivation on employee performance at PT Alfaria Trijaya Tbk, Sampangan Branch, Semarang. Using a quantitative approach, data were collected from 29 employees through Likert-scale questionnaires and analyzed using multiple linear regression. Results show that both compensation (t = 8.56, p < 0.05) and motivation (t = 7.81, p < 0.05) significantly influence employee performance. The model explains 74.8% of performance variance (R² = 0.748), confirming equity and expectancy theories' relevance in retail contexts. These findings suggest that fair compensation systems and effective motivational strategies are critical for optimizing retail employee performance, providing practical insights for Alfamart management and contributing to HR management literature in Indonesia's retail industry.